Students' Ability to Communicate in Speaking Learning through an Active Learning Approach for High School Students - Muslim Muslim; Arsad Arsad; Risman Iye (AIQU: Journal Multidiscipliner of Science, 2023)
This research aims to determine students' ability to communicate in speaking lessons through an active learning approach in class XI students at SMA Muhammadiyah 1 Baubau. The method used in this research is a quantitative descriptive research method. The quantitative descriptive method is a research design that clearly and realistically describes research variables in the form of numbers and statistics. This type of research includes field research. It is said to be field research (respondents) and researchers are directly involved in collecting data. Based on the tabulation results, it can be seen that the average student score in the pressure aspect is 15 out of a weighted score of 190 in the sufficient category, then the average student score in the grammar aspect is 20 out of a weighted score of 265 in the good category, and the average score -The average student score in the vocabulary aspect is 20 out of a weighted score of 245 in the good category, while the average student score in the fluency aspect is 15 out of a weighted score of 225 in the sufficient category. Furthermore, the determination of all aspects is 925 with an average student score of 65 or 65%. Thus, the student category in all aspects is the sufficient category.